Analisis Semiotika pada Puisi Ini Sandiwara Apa Karya Eka Nurul Hayat - Asmi Sihombing, Novita (J-LELC: Journal of Language Education, Linguistics, and Culture, 2023)
Semiotic analysis of the poem "This is Sandiwara Apa" by Eka Nurul Hayat is discussed in this post. Aspects of the characteristics that appear in the poem are analyzed. Poetry is an expression of the soul through words that have aesthetic value, have an inner and physical structure, and have several indicators of both meaning and language. The bond between poetry and objects outside the work influences the interpretation and meaning of poetry in its totality. The study of poetry through semiotics introduces how poetry is studied and enjoys its characteristics. Semiotics helps master and build poetry so that it shares descriptions with readers. Therefore, mastering semiotics is very meaningful because language and semiotics are inseparable. In semiotic analysis, the writer reads and masters the contents of the work, then analyzes meaning making, hypograms, hermeneutics, and meaning making. The poem "This Is a Sandiwara Apa" by Eka Nurul Hayat has a close affinity with symbols and shares interpretations of everyday life. The poet gives a reflection about the meaning of not carrying out a disgraceful act by wearing a mask.